On the Puzzle of Diversification in Social Networks with Occupational Mismatch - Anna Zaharieva (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper incorporates social networks into a frictional labour market framework. There are two worker types and two occupations. Both occupations are subject to correlated business cycle fluctuations in labour demand. The equilibrium in this model is characterized by occupational mismatch which is associated with a wage penalty. This paper shows that there exists a unique value of network homophily maximizing the present value of income. Therefore, there is a gain for risk-neutral workers if their network is diversified between the two occupations. The reason for diversification is that the present value of income is a non-linear function of the network composition. Thus, it is not the desire to reduce the volatility of income as in standard portfolio theory which is driving the decision of workers. Nevertheless, the optimal diversification level is higher with stronger negative correlation in labour demand between the two occupations, with a lower unemployment benefit and with a higher probability of recession in the primary occupation. On the other hand, the optimal diversification level is reduced if there is on-the-job search in the state of mismatch.
Keywords: J64; J46; J22; 330